Investigation of Drought Characteristics Across Vietnam During Period 1980-2018 using SPI and SPEI Drought Indices - Duc, Tran Quang; Thao, Nguyen Phuong; Long, Trinh Tuan; Van Tan, Phan; Thi Thu Huong, Chu; Van Hiep, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2022)
In this study the drought characteristics, trend of change and relationship between drought over Vietnam and large scale processes were investigated using drought indices of SPI and SPEI. The monthly mean temperature and precipitation data collected from 146 stations of Vietnam for the period 1980-2018 and datasets of monthly climate indices were used. The drought characteristics, including drought frequency, drought duration, drought severity and drought spatial extent, were investigated for three time scales of 3-month, 6-month and 12-month droughts. Trend of drought change was estimated using Mann-Kendal test and Sen’s slopes. The relationship between drought and large scale processes were examined based on correlation coefficients of drought indices and climate indices as well as their empirical orthogonal functions. The obtanied results showed that there is no distinction between drought characteristics calculated from SPI and SPEI but drought characteristics are significant different among drought time scales. Effects of temperature on drought are only reflected in the trend of change in drought indices. Both SPI and SPEI indices showed that drought frequency and drought duration are larger in the northern sub-regions than that in southern sub-regions. Drought in the southern sub-regions is strongly associated with the ENSO indices. In the North Central and a part of South Central drought is somewhat related to the multi-year variability of the SST over Pacific and Atlantic oceans, while in the three northern sub-regions drought is slightly correlated with climate indices.